2012
DOI: 10.18060/1874
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of PTSD in Older Veterans: The Posttraumatic Stress Disorder Checklist: Military Version (PCL-M)

Abstract: The Posttraumatic Stress Disorder (PTSD) Checklist: Military Version (PCL-M) is a 17-item, self-report measure of PTSD symptomatology in military veterans and provides one total score and four subscale scores for older veterans’ PTSD (re-experiencing, avoiding, numbing, and hyperarousal symptoms). Study subjects are 456 male veterans over 55-years old with deployed experiences selected from a larger survey data by Veterans’ Affairs Canada (VAC). This study found that overall scale reliability was excellent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…While the original PCL-M asks about posttraumatic symptoms in the past month related to stressful military experiences, in this study respondents were asked about stressful work experiences. The PCL-M has been validated in multiple samples; previous studies have reported Cronbach's >.90 (e.g., Blanchard et al, 1996, Weathers et al, 1993, Yarvis et al, 2012. In this sample, the PCL-M also demonstrated high reliability ( =.98).…”
Section: Methodsmentioning
confidence: 66%
“…While the original PCL-M asks about posttraumatic symptoms in the past month related to stressful military experiences, in this study respondents were asked about stressful work experiences. The PCL-M has been validated in multiple samples; previous studies have reported Cronbach's >.90 (e.g., Blanchard et al, 1996, Weathers et al, 1993, Yarvis et al, 2012. In this sample, the PCL-M also demonstrated high reliability ( =.98).…”
Section: Methodsmentioning
confidence: 66%
“…For these outcomes, we found an association between clinician‐rated and self‐reported symptoms for the younger group, but not for the older group. Previous studies (Cook et al., ; Yarvis et al., ) found the PCL to have adequate reliability and validity in older civilian and veteran samples, but neither of these studies compared self‐reported PTSD with clinician‐rated symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, no study has directly compared the association between clinician‐ and self‐assessments of PTSD symptoms in older versus younger adults. Based on past studies of the PCL (e.g., Cook et al., ; Yarvis et al., ), and Monson et al. 's () study showing a high degree of association between the PCL and the CAPS, we expected that the two measures would be strongly associated.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It should be noted that chi-square statistic can be influenced by sample size, and thus should be examined carefully (Kline, 2011). The standardized RMSR (SRMSR) should have a value of ≤.05 and incremental fit index (IFI) should have a value of ≥.90 (Yaris, Yoon, Amenuke, Simien-Turner, & Landers, 2012). Principal axis exploratory factor analysis is a commonly used method for establishing construct validity.…”
Section: Purposementioning
confidence: 99%